Critical laboratory values - an experience in Apollo Hospitals Dhaka - Ibrahim, M; Islam, I; Nasir, TA; Saha, D (Pulse, 2010)
Reporting of laboratory critical values has become important for patient safety as described by recent guidelines in National Patient Safety Goals of the Joint Commission on Accreditation of Healthcare Organizations (JCAHO). The use of critical values reporting was adopted as a requirement in the Clinical Laboratory Improvement Amendments (CLIA'88). Herein, we reported the results of an analysis of 4260 consecutive laboratory critical values from July 2007 to June 2008 at our institution, a large tertiary medical center. We evaluated critical value reporting by parameters, laboratory speciality (Clinical Chemistry & Hematology), clinical care area (IPD, OPD, Emergency), and Turn around time. Factors leading to delays in critical value reporting are identified, and we describe approaches to improving this important operational and patient safety. DOI: 10.3329/pulse.v3i1.6544 Pulse Vol.3(1) July 2009 p7-11